Trends in Multicultural Education Publication Over a Four-Decade Period: A Bibliometric Review - Roni Rodiyana; Bunyamin Maftuh; Sapriya Sapriya; Ernawulan Syaodih; Davi Sofyan (UIN Siber Syekh Nurjati Cirebon, 2022)
AbstractThe objective of this study is to systematically review academic works in the area of multicultural education. Publications were gathered using the Scopus database and a variety of bibliometric variables. The publishing mapping program VOS viewer was used to analyzing the collected data. There were 501 publications on intercultural and multicultural education that were published between 1973 to 2021. The results showed that between 1973 and 2021, the number of publications varied. With the addition of 12 publication documents, the number of publications has doubled starting in 1997. The most published documents amounted to 42 in 2020. The number of academic scientific papers published in the United States, which is recognized as the most productive nation, is 321. Constantine, M.G., of Columbia University in the United States, is the most prolific writer. With 14 publications, Columbia University in the US was the most productive university. The findings of this study imply that the main keyword is